The Chinese from Indonesia in the Netherlands and their heritage; Chinese Indonesian Heritage Center (CIHC) - Liem, Patricia Tjiook (Wacana, Journal of the Humanities of Indonesia, 2017)
Chinese from Indonesia in the Netherlands are (post)colonial migrants who share a long historical tie with the Dutch. In this article the author brings together and focuses on three interconnected subjects: Chinese from Indonesia in the Netherlands; the historical development and present meaning of "heritage"; and the Chinese Indonesian Heritage Center (CIHC). For her research on the Chinese Indonesians in the Netherlands, the author has used the literature available on this minority group. The scarce specific data for this group are part of the explanation of its "invisibility" in society and research, and of the difficulty in quantifying them. The development of heritage as a western concept has led her to the question of what heritage might mean for migrants in their new homeland. The concluding part on the Chinese Indonesian Heritage Center introduces the activities of the Center designed to achieve her goals which are focused on the history of this group.